Systematic review: efficacy of escalated maintenance anti‐tumour necrosis factor therapy in Crohn's disease. Issue 3 (21st June 2021) - Mattoo, Vandita Y.; Basnayake, Chamara; Connell, William R.; Ding, Nik; Kamm, Michael A.; Lust, Mark; Niewiadomski, Ola; Thompson, Alexander; Wright, Emily K.
Summary: Background: Loss of response to anti‐TNF agents is a common clinical problem. Dose escalation may be effective for reestablishing clinical response in Crohn's disease (CD). Aims: To perform a systematic review assessing the efficacy of escalated maintenance anti‐TNF therapy in CD. Methods: EMBASE, MEDLINE, Web of Science, and CENTRAL databases were searched for English language publications through to April 25, 2021. Full‐text articles evaluating escalated maintenance treatment (infliximab or adalimumab) in adult CD patients were included. Results: A total of 4733 records were identified, and 68 articles met eligibility criteria. Rates of clinical response (33%‐100%) and remission (15%‐83%) after empiric dose escalation for loss of response to standard anti‐TNF therapy were high but varied across studies. Dose intensification strategies (doubling the dose versus shortening the therapeutic interval) were similarly efficacious. Dose‐escalated patients tended to have higher serum drug levels compared to those on standard dosing. An exposure‐response relationship following dose escalation was found in a number of observational studies. Randomised controlled trials comparing therapeutic drug monitoring (TDM) to empiric treatment intensification have failed to reach their primary end‐points. Strategies including Bayesian dashboard‐dosing and early treatment escalation targeting biomarker normalisation were found to be associated with improved long‐term outcomes. Conclusions: Empiric escalation of maintenance anti‐TNF therapy can recapture clinical response in a majority of patients with secondary loss of response to standard maintenance doses. Proactive optimisation of maintenance dosing might prolong time to loss of response in some patients. Abstract : Rates of clinical response (33%‐100%) and remission (15%‐83%) after empiric dose escalation for loss of response to standard anti‐TNF therapy were high but varied across studies.Dose intensification strategies (dose doubling vs shortening the therapeutic interval) were similarly efficacious.The role of proactive therapeutic drug monitoring in guiding treatment escalation is uncertain. Biomarker normalisation may be a helpful target in driving anti‐TNF dose escalation, however, this approach requires validation in clinical practice.